2009
DOI: 10.1016/j.febslet.2009.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of multiple curcumin synthases from the herb Curcuma longa

Abstract: Edited by Ulf-Ingo Flügge Keywords:Polyketide synthase Curcumin Demethoxycurcumin Bisdemethoxycurcumin Curcuma longa a b s t r a c t Curcuminoids are pharmaceutically important compounds isolated from the herb Curcuma longa. Two additional type III polyketide synthases, named CURS2 and CURS3, that are capable of curcuminoid synthesis were identified and characterized. In vitro analysis revealed that CURS2 preferred feruloyl-CoA as a starter substrate and CURS3 preferred both feruloyl-CoA and p-coumaroyl-CoA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 16 publications
(44 reference statements)
3
78
0
2
Order By: Relevance
“…DCS and CURS1 were also chosen to test the curcuminoids production due to the promising results previously reported in vitro [9,10,16]. Although these two genes were successfully expressed in E. coli and the enzymes were used to produce several curcuminoids, including curcumin, DCS and CURS1 were never tested in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DCS and CURS1 were also chosen to test the curcuminoids production due to the promising results previously reported in vitro [9,10,16]. Although these two genes were successfully expressed in E. coli and the enzymes were used to produce several curcuminoids, including curcumin, DCS and CURS1 were never tested in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…CURS2 was also reported to prefer feruloylCoA and CURS3 favored both feruloy-CoA and p-coumaroyl-CoA [10]. Since curcumin has been reported to possess, in some systems, a higher therapeutic value than the other curcuminoids [17], CURS1 was chosen as it has the highest turnover rate towards feruloyl-CoA, as well as the highest difference between the catalytic efficiency towards feruloyl-CoA and p-coumaroyl-CoA [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CURS2 uses feruloyl-CoA as a preferred starter substrate, and CURS3 prefers both feruloyl-CoA and 4-coumaroyl-CoA. Based on their substrate preference, CURS2 can synthesize curcumin and demethoxycurcumin, whereas CURS3 may synthesize curcumin, bisdemethoxycurcumin, and demethoxycurcumin (18). The presence of three similar enzymes and their substrate specificity may explain the natural mixture of these curcuminoids from C. longa.…”
Section: Plant Type III Pkssmentioning
confidence: 99%
“…The same authors identified and characterized two other type III PKS from turmeric, named CURS2 and CURS3 (102). In vitro analysis revealed that CURS2 preferred feruloyl-CoA as the substrate, while CURS3 used both feruloyl-CoA and p-coumaroylCoA (Table 2).…”
Section: Curcuminoid Production In Curcuma Longamentioning
confidence: 99%